FUNCTIONAL, PASTING AND SENSORY PROPERTIES OF COMPLEMENTARY FOOD FROM ORANGE FLESHED SWEETPOTATO- ROASTED AFRICAN YAM BEAN-TIGERNUT COMPOSITE FLOUR USING RESPONSE SURFACE METHODOLOGY - Omobolanle Omowunmi OLORODE; Emmanuel Kehinde OKE; Pius Alaba AGBEBI; Adebola Atinuke ALABI; Femi Fidelis AKINWANDE (Food and Environment Safety, 2022)
This study investigated the functional, pasting and sensory properties of complementary food from blends of orange fleshed sweet potato, roasted African yam bean and tigernut composite flour using response surface methodology. Orange fleshed sweetpotato root, roasted African yam bean and tigernut seed were blended into composite flours based on D-optimal mixture design resulting into fourteen experimental runs. The Orange fleshed sweetpotato, roasted African yam bean and tigernut flour blends were analyzed for their functional and pasting properties using standard laboratory procedures. The composite flours were optimized using D-optimal of the mixture design. The optimized composite flours were used to prepare complementary food and sensory properties (taste, colour, aroma, thickness and overall acceptability) were evaluated using nine point Hedonic scale of preference. The bulk density, water absorption capacity, swelling power, dispersibility, least gelation capacity and wettability ranged from 0.82-0.85g/ml, 300.00-359.00%, 6.00-6.51%, 60.20-65.99%, 2.72-3.69% and 22.71to 40.81% respectively. Significant differences (p<0.05) were observed in the pasting properties of orange fleshed sweetpotato, roasted African yam bean and tigernut flour blends. However optimized complementary prepared from the different composite flours were all accepted by the panelists except complementary food prepared from 82.95% orange fleshed sweetpotato, 10.26% roasted African yam bean and 6.78% tigernut composite flour blend.